2015
DOI: 10.1007/s00125-015-3692-7
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide binding protein is an adipokine involved in the resilience of the mouse adipocyte to inflammation

Abstract: Aims/hypothesis Lipopolysaccharide (LPS) binding protein (LBP) is a novel 65 kDa adipokine, linked to adipose tissue (AT) inflammation, obesity and insulin resistance, that inhibits adipocyte differentiation. Here, we investigated the molecular mechanisms behind these detrimental effects on adipogenesis through whole-genome transcriptomics and in vitro experiments. Methods Permanent and transient knockdown (KD) and coculture experiments were performed in 3T3-L1 and 3T3-F442A cell lines during adipocyte differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…However, more high‐quality evidence is required to support this hypothesis. In addition, genes related to lipopolysaccharide biosynthesis proteins and bacterial invasion of epithelial cells were increased, which indicates that candidate pathogenic commensals might attach the colonic epithelial cells and facilitate the development of obesity via inflammation‐related mechanisms . Genes related to glycolysis, gluconeogenesis, and the pentose phosphate pathway were decreased in obesity, which partly explained the lower ability of the body to utilize glucose.…”
Section: Discussionmentioning
confidence: 99%
“…However, more high‐quality evidence is required to support this hypothesis. In addition, genes related to lipopolysaccharide biosynthesis proteins and bacterial invasion of epithelial cells were increased, which indicates that candidate pathogenic commensals might attach the colonic epithelial cells and facilitate the development of obesity via inflammation‐related mechanisms . Genes related to glycolysis, gluconeogenesis, and the pentose phosphate pathway were decreased in obesity, which partly explained the lower ability of the body to utilize glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, moderately increased LPS in circulation, or metabolic endotoxemia, in response to a high-fat diet was shown to trigger obesity and insulin resistance in mice [42, 43]. Several studies also showed that LBP is produced by adipocytes and plays an essential role in inflammation- and obesity-associated adipose tissue dysfunction [44, 45]. The relationship between LBP and obesity, insulin resistance, and the metabolic syndrome has been demonstrated in a number of studies performed in humans in both cross-sectional [8, 9, 11, 12] and prospective [10, 13] designs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its immunostimulatory functions [14], LBP has been identified as an adipokine associated with obesityinduced metabolic and proinflammatory disorders [15,16]. The promotion of BAT activity and, especially, of WAT browning are active research areas that hold promise for strategies aimed at protecting against obesity and associated metabolic abnormalities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…LBP knockdown and co-culture experiments Stable silencing of Lbp was achieved by transfecting 3T3-L1 fibroblasts with small hairpin (interfering) RNA (shRNA) targeting mouse Lbp (shLBP)or control shRNA (shControl) (Sigma Mission shRNA; Sigma-Aldrich, St Louis, MO, USA) as previously reported [16], generating transfected cells described in this paper as shRNA-mediated LBP knockdown (shLBP) or control (shControl) cells, respectively. Where indicated, shLBP adipocytes were incubated with 10 ng/ml LBP (R&D Systems; Minneapolis, MN, USA) during differentiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation